Efektivitas Program Magang Bersertifikat dalam Meningkatkan Kesiapan Kerja Mahasiswa Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau - Gunawan, Meylisha; Bedasari, Hafzana (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
The increasingly competitive demands of the job market require university graduates to not only possess academic knowledge but also relevant practical experience aligned with industry needs. To address this challenge, the Ministry of Education, Culture, Research, and Technology launched the Certified Internship Program as part of the Merdeka Belajar Kampus Merdeka (MBKM) policy. This study aims to analyze the effectiveness of the Certified Internship Program in enhancing the job readiness of students in the Faculty of Social Sciences and Political Science at the University of Riau. The research method used is a qualitative approach with data collection techniques through interviews and documentation. Analysis was conducted using five program effectiveness indicators according to Sutrisno's theory, namely program understanding, target accuracy, timeliness, achievement of objectives, and tangible changes. The research results indicate that the Certified Internship Program is not yet effective, with several challenges still identified, such as delays in the selection and administrative processes, uneven program dissemination, and mismatches between internship positions and fields of study. These findings emphasize the need for adjustments to internship positions, improvements in administration, and broader program outreach. The contribution of this research provides strategic input for the development of internship policies on campus to be more adaptive to labor market needs.